Catwad. It's me - Benton, Jim (Graphix, 2019)
A grouchy, blue-colored cat named Catwad hates everything, but his best friend Blurmp is a happy-go-lucky orange-hued cat who seems able to see the bright side of absolutely anything. Together, they make a comic pair in any situation.